Impact of Paternal Age on Seminal Parameters and Reproductive Outcome of Intracytoplasmatic Sperm Injection in Infertile Italian Women - Gallo, Mariagrazia; Licata, Emanuele; Meneghini, Caterina; Dal Lago, Alessandro; Fabiani, Cristina; Amodei, Marcello; Antonaci, Domenico; Miriello, Donatella; Corno, Roberta; Liberanome, Carmelina; Bisogni, Francescantonio; Paciotti, Gemma; et al. (Frontiers in Endocrinology, 2019)
Background: We conducted a retrospective study on a cohort of couples attending the Department of Andrology and Reproductive Pathophysiology at Sandro Pertini Hospital in Rome for Intracytoplasmatic Sperm Injection (ICSI) -assisted reproduction programs. Some of the couples included in the study underwent more than one ICSI cycle. Between January 2015 and April 2017. Objective: To evaluate whether the advancing of the paternal age may have effect on the seminal parameters, thus negatively affecting the embryo formation, development and quality, as well as the pregnancy rate. Materials and Methods: 543 ICSI cycles were performed on 439 couples undergoing Assisted Reproductive Technologies (ART). Patients were subdivided into three male and three female age groups having similar size: Men: ≤38 years (MI), 39-43 years (MII), ≥44 years (MIII). Women: ≤35 years (FI), 36-40 years (FII),>41 years (FIII). Discussion and Conclusion: Male age groups did not reveal any statistical significant differences in any age-related semen parameters. We also confirmed a statistical significant increase in the pregnancy rate of couples with older partner age difference and younger female. We found that the advanced male age increases the probability of obtaining one or no type A embryo (NA ≤1), which was almost doubled in the MIII group in comparison with MI, suggesting a negative effect of male age on the efficacy of the reproductive outcome in terms of a reduced number of type A embryos. Such effect does not seem related to semen parameters and may deserve further investigations.